FEATURES OF THE NARRATIVE OF THE INTELLECTUAL DETECTIVE D. BROWN "THE LOST SYMBOL" - Хамракулов Тимур Пулатович (Western European Studies, 2024)
The article is devoted to identifying the features of the structure and functions of the narrative in the intellectual detective story “The Lost Symbol”. It is noted that the montage composition of the chapters creates tension in the narrative, contributes to the subordination of the investigation to a certain time, and enhances the internal focalization of R. Langdon - the intellectual investigator and anti-hero Malakh. D. Brown uses the parameters of the crime genre (time and space) to demonstrate “ambiguity.” Graphically, the features of the narrative are contained in italics of those phrases of the “internal monologue” of the characters that are semantically important for the author.
Keywords: narrative; montage composition; intellectual detective; time and space